Rheumatoid Arthritis-Associated Interstitial Lung Disease: Diagnostic Dilemma - Mark J. Hamblin; Maureen R. Horton (Pulmonary Medicine)
Interstitial lung disease (ILD) is an increasingly recognized complication of rheumatoid arthritis (RA) contributing to significantly increased morbidity and mortality. Diagnosis can be challenging since patients are unlikely to report dyspnea due to an overall decrease in physical activity with advanced arthritic symptoms. Additionally, infections, drug toxicity, and environmental toxins can mimic ILD, creating significant diagnostic dilemmas for the clinician. In this paper we will explore an effective clinical algorithm for the diagnosis of RA-ILD. We will also discuss features of drug-related toxicities, infections, and environmental toxins that comprise the main entities in the differential diagnosis of RA-ILD. Finally, we will explore the known and experimental treatment options that may have some benefit in the treatment of RA-ILD.